Stability of lactic acid bacteria in synbiotic sugared and sugar-free milk chocolates - Toker, Omer Said; Polat, Derya Genc; Gulfidan, Osman Gokhan; Konar, Nevzat; Palabiyik, Ibrahim; Akcicek, Alican; Poyrazoglu, Ender Sinan; Sagdic, Osman (TAYLOR & FRANCIS INC, 2017)
In this study, stability of Lactobacillus acidophilus and L. paracasei in synbiotic sugared and sugar-free milk chocolates within 90-day storage was investigated, considering inline as prebiotic. Probiotic bacteria inoculation at 9.0 log cfu/25 g and usage of inulin with Degree of Polymerisation (DP) 23 at a concentration of 9.0 g/100 g were investigated. At the end of 90 days, at least 6.5 log cfu/25 g probiotic bacteria was determined in the samples containing L. acidophilus, whereas this value was determined as 5.9 log cfu/25 g for L. paracasei. Therefore, it was concluded that L. acidophilus was more stable in terms of viability level in the milk chocolates prepared by sugar, maltitol, and inulin DP was effective on viability levels of probiotics (p < 0.05). Moreover, inulin DP was also found effective on water activity, melting, rheological and textural properties and colour of milk chocolate (p < 0.05). Quality parameters were affected by inulin DP, except rheological properties.
Keywords: Chocolate; Inulin; Lactobacillus; Maltitol; Probiotic; RHEOLOGICAL PROPERTIES; DARK CHOCOLATE; PROBIOTIC BACTERIA; SWEETENERS; CONFECTIONERY; PRODUCT; STORAGE; IMPACT; FOODS; Food Science & Technology